Pergaminos impresos inventariados en el archivo histórico provincial de León - Burón Castro, Taurino (Estudios humanísticos. Geografía, historia y arte, 1995)
This article shows and catalogues leafs and pieces proceeding from 16 liturgical books printed on parchment. This association has been doing by the point of view of writting support proper the significance of these units in relation to the early printing. The pieces are printed between 1488 and 1567 and add up to 49 leafs, 6 halfleafs, 7 fragments and 3 strips. The stencil, an special printing system, has been mentioned, because it's an appropiate resort to leather printing. Finally has been marked some features of the music sings evolution, which have been influenced by the manuscript, and also by the printed tradition. The bibliography of the page hasn't been included because the text before the catalogue pretends to show the printed papers, not to study them in their different points of view.